Project Management for the Creation of Organisational Value - Zwikael, Ofer.; Smyrk, John.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Projects and programmes are approved and funded to generate benefits. Project Management for the Creation of Organisational Value proposes a complete framework that seeks to support such an objective – from project selection and definition, through execution, and beyond implementation of deliverables until benefits are secured. Because it is preoccupied with deliverables, accepted project management practice is flawed. Project Management for the Creation of Organisational Value proposes an alternative approach, which seeks a flow of target outcomes for the organisation investing in the project. Project Management for the Creation of Organisational Value provides support for all those who play a role of leadership in projects at different levels. Senior executives, practitioners and academics will find in this book a comprehensive guide to the conduct of projects and programmes, which includes robust models, a set of consistent principles, an integrated glossary, enabling tools, illustrative examples and case studies.
1. Projects: An Executive Context -- 2. The Input-Transform-Outcome (ITO) Model of a Project -- 3. Achieving Success in Projects -- 4. The Project Environment -- 5. Starting a New Project -- 6. Planning a Project: The Roles of the Key Players -- 7. Executing a Project: The Roles of the Key Players -- 8. Realising Outcomes from a Project: The Roles of the Key Players.
Keywords: Engineering economics; Engineering economy; Engineering Economics, Organization, Logistics, Marketing